Problems of the exclusion of compulsory insurance due to act classifiable as use of a vehicle at ports and airports (Acta Judicial Journal, 2018)
The 2008 legal reform on the exclusion from the Regulation concerning the compulsory motor insurance demands concretization about the concept of “acts classifiable as use of a vehicle”, as well as the places excluded by the insurance. This qualitative element determines the applicability of the Regulation and produces anomalous effects that generates the contradiction of requiring a voluntary insurance to travel through specific areas at ports and airports.
Keywords: Act classifiable as use of a vehicle, Compulsory insurance, Voluntary insurance, Ports, Airports, Restricted areas.